2014
DOI: 10.1021/mz400520s
|View full text |Cite
|
Sign up to set email alerts
|

Di(cyanate Ester) Networks Based on Alternative Fluorinated Bisphenols with Extremely Low Water Uptake

Abstract: A new polycyanurate network exhibiting extremely low moisture uptake has been produced via the treatment of perfluorocyclobutane-containing Bisphenol T with cyanogen bromide and subsequent thermal cyclotrimerization. The water uptake, at 0.56 ± 0.10% after immersion in water at 85 °C for 96 h, represents some of the most promising moisture resistance observed to date in polycyanurate networks. This excellent performance derives from a near optimal value of the glass transition at 190 °C at full cure. Superior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
(58 reference statements)
2
27
0
Order By: Relevance
“…Water uptake can be alleviated in part through CE monomer development and the incorporation of functional groups that inhibit water absorption through steric or hydrophobic interactions . For example, our research group and others have shown that incorporating some degree of fluorination within CE monomers results in CEs that display some of the lowest water uptake reported to date . Additionally, it has been shown that high conversions of the cyanate groups yields networks with more desirable physical properties, including reduced water uptake .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water uptake can be alleviated in part through CE monomer development and the incorporation of functional groups that inhibit water absorption through steric or hydrophobic interactions . For example, our research group and others have shown that incorporating some degree of fluorination within CE monomers results in CEs that display some of the lowest water uptake reported to date . Additionally, it has been shown that high conversions of the cyanate groups yields networks with more desirable physical properties, including reduced water uptake .…”
Section: Introductionmentioning
confidence: 99%
“…26 For example, our research group and others have shown that incorporating some degree of fluorination within CE monomers results in CEs that display some of the lowest water uptake reported to date. 27,28 Additionally, it has been shown that high conversions of the cyanate groups yields networks with more desirable physical properties, including reduced water uptake. 29,30 When unreacted cyanate groups are present, they can decompose or react with water leading to further degradation and blistering within the network.…”
Section: Introductionmentioning
confidence: 99%
“…1-10 These materials usually show high thermostability, good mechanical properties, excellent insulating behavior and moisture resistance. [11][12][13][14][15][16][17] Therefore, they have played very important roles in the materials utilized in aerospace, electrical and microelectronics industries. However, most of the polymers show unsatisfactory processability, which needs to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…38−44 Alternatively, similar effects can be obtained by altering the bridging groups between rings. 45 −56 In a recent paper we described the synthesis and characterization of a series of bis(cyanate) esters derived from the renewable phenol creosol (2-methoxy-4-methylphenol). 57 Unlike the majority of modified cyanate ester resins that have aliphatic or aromatic substituents, the resins derived from creosol have methoxy groups ortho to the cyanate ester groups.…”
Section: ■ Introductionmentioning
confidence: 99%